Electron Microscopy - Mhadhbi, Mohsen (IntechOpen, 2022)
This book provides an overview of the principles and types of electron microscopes. It also describes the different practical applications of electron microscopes, ranging from particle analysis and materials characterization to industrial failure analysis and process control. Over eight chapters divided into two sections, this book gives readers a comprehensive and updated review of the latest advances in electron microscopy.